Improving Service Quality at Bank Sampah APEL, Sleman Yogyakarta, Through a Digitalization Program - Saidah, Zahrotus; Fitriarti, Etik Anjar; Fajri, Ika Nur; Rohim, Dwi Nur; Ardani, Lutfasari; Putri Anggara, Rindina Adisya; Pangestu, Rafel Alansyah; Setioadi, Rizkiansyah Eka (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2024)
Background: Yogyakarta faces a waste crisis due to the Piyungan landfill closure, with Sleman generating 320 tons of waste daily. Waste Banks like APEL in Sleman manage waste through composting, recycling, and crafting, reducing waste and offering economic benefits. Contribution: The application of excel in the preparation of financial statements will contribute greatly to improve the quality of financial statements presented by BUMDes and have an impact on the effectiveness of decision making which ultimately supports the progress of these BUMDes. Method: APEL employs the 3R system, raising environmental awareness but faces challenges in manual management and limited digital promotion. BUMDes Damar Limo manages diverse transactions and must produce key financial reports. Results: BUMDes Damar Limo of central Bengkulu Region. has CekDam tourism, tourist trains and batik production as main business. Transactions that occur in these BUMdes include receipt of capital deposits, purchases of vehicles, equipment, raw materials, merchandise inventory, and supplies, payment of salaries and other costs, and revenue generation. The reports that must be presented include the income statement, statement of financial position, and statement of BUMdes health. Conclusion: The implementation of the Excel Accounting has an impact on presenting higher quality financial statements and managing BUMDes efficiently and professionally